Philosophy, religion, and the spiritual life - McGhee, Michael (Royal Institute of Philosophy supplement, 1992)
An alternative agenda for the philosophy of religion emerges from this interdisciplinary collection. Going outside the traditional concerns of natural theology, the distinguished contributors to this volume explore such topics as the nature of selfhood and its images in the ancient, the medieval and the modern world; the role of philosophy as a route to wisdom; non-conceptual awareness; and the nature of love and its relation to attention. Discussion focuses on the figures of Plato and Augustine, William James and the Absolute Idealist F. H. Bradley, Kierkegaard and Heidegger, as well as leading figures of the Tibetan Buddhist tradition.